2013
DOI: 10.1093/jpepsy/jst033
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Sleep Duration Alters Emotional Functioning and Cognitive Performance in Children

Abstract: Results suggest that even modest differences in sleep duration over just a few nights can have significant consequences for children's daytime functioning. These findings demonstrate the important impact of sleep duration on children's daytime functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(165 citation statements)
references
References 46 publications
10
147
1
1
Order By: Relevance
“…Four studies were randomized experiments, 11 studies used a longitudinal design, and 47 studies used a cross-sectional design. All 4 randomized trials (Baum et al 2014;Dagys et al 2012;Tamura and Tanaka 2014;Vriend et al 2013) were consistent in showing better emotional regulation in the healthy sleep group compared with the sleep-restricted one. The quality of evidence was rated as high for the randomized trials.…”
Section: Emotional Regulationmentioning
confidence: 79%
See 3 more Smart Citations
“…Four studies were randomized experiments, 11 studies used a longitudinal design, and 47 studies used a cross-sectional design. All 4 randomized trials (Baum et al 2014;Dagys et al 2012;Tamura and Tanaka 2014;Vriend et al 2013) were consistent in showing better emotional regulation in the healthy sleep group compared with the sleep-restricted one. The quality of evidence was rated as high for the randomized trials.…”
Section: Emotional Regulationmentioning
confidence: 79%
“…Only 1 randomized trial examined this association (Vriend et al 2013) and found that short-term memory, working memory, divided attention, and math fluency scores were lower in children in the short sleep condition (1 h later in bed for 4 nights with usual wake-up time) compared with long sleep (1 h earlier for 4 nights relative to their typical bedtime). However, no differences were found for reaction time on alerting, orienting, sustained, or executive attention tasks between long and short sleep conditions.…”
Section: Cognition/academic Achievementmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Furthermore, when facing an emotional challenge (solvable and unsolvable puzzles), nap-deprived children displayed dampened positive emotions to solvable puzzles as well as increased negative emotions to unsolvable puzzles. Vriend and colleagues 9 reported that 1 hour of sleep restriction for 4 consecutive nights resulted in increased sleepiness, less positive affective response to stimuli, and increased difficulty in emotion regulation, in children aged 8 to 12 years. These findings establish a causal influence of sleep on emotional outcomes across childhood.…”
Section: Sleep Disturbances In Infants Arementioning
confidence: 99%